Comparison of outcomes between pulseless electrical activity by electrocardiography and pulseless myocardial activity by echocardiography in out-of-hospital cardiac arrest; secondary analysis from a large, prospective study. (December 2021) - Gaspari, Romolo; Weekes, Anthony; Adhikari, Srikar; Noble, Vicki E.; Nomura, Jason T.; Theodoro, Daniel; Woo, Michael Y.; Atkinson, Paul; Blehar, David; Brown, Samuel M.; Caffery, Terrell; Haines, Christine; et al.
Highlights: Patient in cardiac arrest can have a different electrical rhythm by ECG and myocardial activity by echo. Patients with PEA on ECG can have different activity by echo. Patients with non-shockable rhythms by ECG can show shockable rhythms by echo. Abstract: Objective: To measure prevalence of discordance between electrical activity recorded by electrocardiography (ECG) and myocardial activity visualized by echocardiography (echo) in patients presenting after cardiac arrest and to compare survival outcomes in cohorts defined by ECG and echo. Methods: This is a secondary analysis of a previously published prospective study at twenty hospitals. Patients presenting after out-of-hospital arrest were included. The cardiac electrical activity was defined by ECG and contemporaneous myocardial activity was defined by bedside echo. Myocardial activity by echo was classified as myocardial asystole- -the absence of myocardial movement, pulseless myocardial activity (PMA)--visible myocardial movement but no pulse, and myocardial fibrillation- -visualized fibrillation. Primary outcome was the prevalence of discordance between electrical activity and myocardial activity. Results: 793 patients and 1943 pauses in CPR were included. 28.6% of CPR pauses demonstrated a difference in electrical activity (ECG) and myocardial activity (echo), 5.0% with asystole (ECG) and PMA (echo), and 22.1% with PEA (ECG) and myocardial asystole (echo). Twenty-five percent of the 32 pauses in CPR with a shockable rhythm by echo demonstrated a non-shockable rhythm by ECG and were not defibrillated. Survival for patients with PMA (echo) was 29.1% (95%CI-23.9–34.9) compared to those with PEA (ECG) (21.4%, 95%CI–17.7–25.6). Conclusion: Patients in cardiac arrest commonly demonstrate different electrical (ECG) and myocardial activity (echo). Further research is needed to better define cardiac activity during cardiac arrest and to explore outcome between groups defined by electrical and myocardial activity.